The seed coats of cowpeas and other grain legumes: structure in relation to function - Lush, W.M.; Evans, L.T. (1980)
The structure of the seed coat of a number of grain legumes and their wild relatives was studied in relation to its function and with particular emphasis on cowpeas, Vigna unguiculata (L.) Walp. (V. sinensis (L.) Savi). Structurally all of the seed coats examined, except those of groundnuts (Arachis hypogaea), conformed to the general pattern for legumes, but there was considerable variation in thickness associated with differences in the size of cells. The specific weight of the testas ranged from 30.6 mg cm−2 in Lupinus pilosus to 1.6 mg cm−2 in some cowpeas. Cowpeas have two distinct types of seed coat: that with a rough texture was the thinnest coat found any of the legumes examined; the other was a smooth or thich coat. Intermediate forms were also found. Domesticated legumes had thinner seed coats that were more permeable to water and had larger seeds than their wild relatives. Experiments with cowpeas failed to provide any evidence that a thick testa limits the size of seeds by acting as a mechanical constraint to growth. The smooth testas of dry seeds had a clear role in regulating the loss of water, which occurred through the hilum groove, and its entry, which was through the raphe. It is proposed that differential swelling and contraction of layers within the testa may account for the action of these regions. Rough-seeded lines did not have the capacity to control water exchange, the entire testa being permeable. The selective advantages of thick and thin seed coats to wild and cultivated legumes are discussed and a proposal is made to account for differences in the seed coat thickness found in hard seeds of wild legumes.